2020
DOI: 10.3390/ijerph17113986
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention and Management of COVID-19: Seeking a Practical and Timely Solution

Abstract: We read with interest several manuscripts recently published in the International Journal of Environmental Research and Public Health (IJERPH) on the ongoing coronavirus pandemic. While these articles provide a well-rounded overview on the risk and current status of this virus, we herein add some relevant information on its etiology, prevention and management, especially for resource-limited healthcare systems. The use of protective actions is both complex and expensive. Affordable options are essential to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…Therefore, we understand that the knowledge of the special behavior of COVID-19 requires a multi-scalar analysis [ 29 , 32 ]. Within the intra-urban scale, the spatial analysis can produce revealing knowledge to help policymakers to reduce the COVID-19 spread, aiming one of the stages of the risk mitigation [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we understand that the knowledge of the special behavior of COVID-19 requires a multi-scalar analysis [ 29 , 32 ]. Within the intra-urban scale, the spatial analysis can produce revealing knowledge to help policymakers to reduce the COVID-19 spread, aiming one of the stages of the risk mitigation [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, if we consider the two stages for the risk mitigation, on the one hand, to reduce the spread and, on the other hand, to decrease the disease severity [ 7 ], this research contributes to the first one to reduce the spread, with local perspective (intra-urban scale). A geospatial and spatial-statistical analysis of the geographical dimension of the COVID-19 pandemic can be considered to understand the spatiotemporal dynamics of COVID-19 and the likelihood of new outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Potent antioxidant activity may contribute to the ability of the indoleamine hormone melatonin, which has also been suggested as an adjuvant therapy for COVID-19 ( Martín Giménez et al, 2020 ; Reiter et al, 2020 ), to ameliorate several adverse consequence of aging. The dipeptide carnosine, which is able to scavenge both ROS and reactive carbonyls ( Hipkiss et al, 2016 ), has been suggested for treating COVID-19 in ( Jindal et al, 2020 ).…”
Section: Covid-19 Vs Agents Suggested For Use Against Aging Based Onmentioning
confidence: 99%
“…PubMed search strategy yielded only three publications with commentaries on using carnosine and salicyl-carnosine, suggested for patients with COVID-19 [37][38][39]. In these papers, carnosine and Our preliminary molecular docking of carnosine added more rationale to recommend further detailed docking and experimental validation and testing for this relatively safe natural supplement in patients with COVID-19.…”
Section: Literature Evaluationmentioning
confidence: 99%